Transdifferentiation of pancreatic ductal cells to endocrine β-cells. (21st May 2008) - Bonner-Weir, Susan; Inada, Akari; Yatoh, Shigeru; Li, Wan-Chun; Aye, Tandy; Toschi, Elena; Sharma, Arun
Abstract : The regenerative process in the pancreas is of particular interest, since diabetes, whether Type 1 or Type 2, results from an inadequate amount of insulin-producing β-cells. Islet neogenesis, or the formation of new islets, seen as budding of hormone-positive cells from the ductal epithelium, has long been considered to be one of the mechanisms of normal islet growth after birth and in regeneration, and suggested the presence of pancreatic stem cells. Results from the rat regeneration model of partial pancreatectomy led us to hypothesize that differentiated pancreatic ductal cells were the pancreatic progenitors after birth, and that with replication they regressed to a less differentiated phenotype and then could differentiate to form new acini and islets. There are numerous supportive results for this hypothesis of neogenesis, including the ability of purified primary human ducts to form insulin-positive cells budding from ducts. However, to rigorously test this hypothesis, we took a direct approach of genetically marking ductal cells using CAII (carbonic anhydrase II) as a duct-cell-specific promoter to drive Cre recombinase in lineage-tracing experiments using the Cre-Lox system. We show that CAII-expressing pancreatic cells act as progenitors that give rise to both new islets and acini after birth and after injury (ductal ligation). This identification of a differentiated pancreatic cell type as an in vivo progenitor for all differentiated pancreatic cell types has implications for a potential expandable source for new islets for replenishment therapy for diabetes either in vivo or ex vivo .